2014
DOI: 10.1097/ico.0000000000000135
|View full text |Cite
|
Sign up to set email alerts
|

Donor Tissue Characteristics in Preparation of DMEK Grafts

Abstract: Exclusion of the contralateral eye tissue when there was difficulty in graft peeling for the first eye may prove to be a unique quality of DMEK donor tissue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
29
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 11 publications
3
29
2
Order By: Relevance
“…PDEK in its current established form was proposed by Dua and first performed by Agarwal et al 10. The fact that a type 1 BB can be created in donors of any age (our unpublished observations) would allow very young tissue with consequent higher endothelial counts to be used for PDEK compared with the conventional stripping technique used to obtain tissue for DMEK wherein it is recognised that the risk of tissue loss is greater in older donors 13 14. Moreover, the support afforded by DL makes the tissue easier to handle and unroll in the eye compared with DM alone 10.…”
Section: Discussionmentioning
confidence: 87%
“…PDEK in its current established form was proposed by Dua and first performed by Agarwal et al 10. The fact that a type 1 BB can be created in donors of any age (our unpublished observations) would allow very young tissue with consequent higher endothelial counts to be used for PDEK compared with the conventional stripping technique used to obtain tissue for DMEK wherein it is recognised that the risk of tissue loss is greater in older donors 13 14. Moreover, the support afforded by DL makes the tissue easier to handle and unroll in the eye compared with DM alone 10.…”
Section: Discussionmentioning
confidence: 87%
“…In this latter context, difficulty in graft peeling for the first eye has been shown to be the most important factor for failure in the fellow eye. 11,15 Also, ultrastructural abnormalities (peg-like interlockings) or biochemical abnormalities (increased staining intensities for adhesive glycoproteins) along the Descemet membrane–stroma interface have been proposed as the main cause of tears during unsuccessful preparation. 16 A recognized association for this is young donor age, which represents a risk factor for DMEK graft preparation failure.…”
Section: Discussionmentioning
confidence: 99%
“…16 A recognized association for this is young donor age, which represents a risk factor for DMEK graft preparation failure. 10,11,16 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although we witnessed a higher adhesion (n = 3) and a tendency for tearing (n = 4) in those selected eyes, successful dissection was achieved in 99 % (85 of 86 eyes). It has been recently shown that donor corneas with preceding cataract surgery and diabetes mellitus are more adherent and difficult to prepare and show a higher risk for unsuccessful preparation [13,14]. It would be very interesting to know something about the cornea donors, especially concerning the status of the lens and the internal diseases.…”
Section: Discussionmentioning
confidence: 98%